Adoption of advanced technological solutions in Slovenian private security companies - Dvojmoč, Miha (Varstvoslovje, 2021)
Purpose: The use of advanced technological solutions in security is one of the current development trends in the private security industry. It represents an opportunity for upgrading security services and for resolving human resources issues that private security companies face. The aim of the article is to present the potentials of modern technological solutions for upgrading security services and overcoming contemporary challenges in the field of private security. Design/Methods/Approach: For the purpose of the study, we conducted interviews with representatives of the Slovenian private security profession to determine the current challenges in the private security industry, their positions on modern technologies and their feasibility in practice. Interviews were conducted at the head offices of respondents’ companies in summer 2019. In total, four interviews were conducted. Findings: The results show that general problems on the labour market have a significant impact on private security services in Slovenia, while the lack of competent personnel leads to unregulated working conditions and the inability to provide quality security services. The implementation of advanced technological solutions could address key operational challenges and optimise financial and human resources. Research Limitations/Implications: One of the limitations of the study is the small number of interviews. We tried to overcome this limitation by carefully selecting the interviewees and by conducting a thorough, in-depth interview. Originality/Value: The study addresses current and important issues and connects with the concepts of digitalisation of companies. This is a topic that is important in both public policing and private policing. The paper thus upgrades and complements existing knowledge in this field.
Keywords: advanced technological solutions; development trends; human resources issues; kadrovska vprašanja; napredne tehnološke rešitve; private security companies; technical security; tehnično varovanje; trendi razvoja; zasebna varnostna podjetja